2019
DOI: 10.3892/ijo.2019.4777
|View full text |Cite
|
Sign up to set email alerts
|

Harmine induces anticancer activity in breast cancer cells via targeting TAZ

Abstract: Harmine (HM) is a β-carboline alkaloid found in multiple medicinal plants. It has been used in folk medicine for anticancer therapy; however, the molecular mechanism of HM on human breast cancer remains unclear. Transcriptional co-activator with PDZ-binding motif (TAZ), also known as WW domain-containing transcription regulator 1, serves an important role in the carcinogenesis and progression of breast cancer. The aim of the present study was to elucidate the potential anticancer activity and mechanism of HM i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 54 publications
1
32
0
1
Order By: Relevance
“…Previous studies have shown that, at high concentrations (above 15-20 uM), harmine exerts significant anti-proliferative and cytotoxic (pro-apoptotic) activities in different types of cancer, consistently with our observations. In these studies, harmine acted with IC50s ranging from 50 to 160 uM [40][41][42]. At high concentrations, harmine was found to act by several mechanisms, described in different cell types and experimental conditions.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have shown that, at high concentrations (above 15-20 uM), harmine exerts significant anti-proliferative and cytotoxic (pro-apoptotic) activities in different types of cancer, consistently with our observations. In these studies, harmine acted with IC50s ranging from 50 to 160 uM [40][41][42]. At high concentrations, harmine was found to act by several mechanisms, described in different cell types and experimental conditions.…”
Section: Discussionmentioning
confidence: 95%
“…At high concentrations, harmine was found to act by several mechanisms, described in different cell types and experimental conditions. These mechanisms include inhibition of the expression levels of the TAZ transcriptional co-activator [40], the epithelial-mesenchymal transcription factor TWIST [42] and STAT3 transcription factor [41], inhibition of the phosphorylation of ERK and Akt [40,43], as well as inhibition of the anti-apoptotic Bcl2 protein and induction of the pro-apoptotic Bax protein [40]. However, those mechanisms were not observed at lower harmine concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to inducing Twist1 degradation, harmine can also inhibit breast cancer cell proliferation and migration by inhibiting the expression of TAZ [ 27 ]. TAZ is a downstream effector of the Hippo pathway that plays an important role in mammalian development [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In MDA-MB-231 breast cancer cells that overexpress breast cancer resistance protein (BCRP), harmine inhibits BCRP [ 26 ]. Harmine is also reported to antagonize transcriptional coactivator with PDZ-binding motif (TAZ), suppress breast cancer cell proliferation and migration, and promote cancer cell apoptosis in vitro [ 27 ]. Recently, in an unbiased screen, harmine was identified as the first pharmacologic inhibitor of Twist1 with significant anti-tumor activity in oncogene-driven lung cancer [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…It causes DNA frameshift mutation and cytotoxic effects that is occurred by a signi cant inhibition of telomerase activity [9] [10]. Also, harmine was found to induce apoptosis in human breast cancer cell line by downregulation of TAZ gene which encodes tafazzin protein [11].…”
Section: Introductionmentioning
confidence: 99%